1993
DOI: 10.1007/bf01886226
|View full text |Cite
|
Sign up to set email alerts
|

In vitro availability of iron from selected nuts and oilseeds

Abstract: Availability of iron from sixteen varieties of selected nuts and oilseeds was assessed by in vitro method. Wide and significant variations were recorded in the contents of total and ionisable iron and in the bioavailability of iron of the nuts and oilseeds. The total iron content was the highest in nigre seeds and the lowest in linseed seeds. Bioavailability of iron was significantly high from pistachio nut and almond and markedly low from groundnut. Most of the nuts and oilseeds were found to have less than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…In groundnut flour, bioaccessibility of iron was 1.25% and that of zinc was 11.3%. Our results confirm the findings of Reddy & Hotwani (1993), who have reported that the ionisable iron in groundnut flour is comparatively lower than all other oilseeds. Lower bioaccessibility of iron in groundnut flour can be attributed to the presence of higher phytate, tannin and oxalate content than soya.…”
Section: Resultssupporting
confidence: 93%
“…In groundnut flour, bioaccessibility of iron was 1.25% and that of zinc was 11.3%. Our results confirm the findings of Reddy & Hotwani (1993), who have reported that the ionisable iron in groundnut flour is comparatively lower than all other oilseeds. Lower bioaccessibility of iron in groundnut flour can be attributed to the presence of higher phytate, tannin and oxalate content than soya.…”
Section: Resultssupporting
confidence: 93%
“…Dialysability of iron representing bioaccessibility increased by almost twofold from defatted flour to protein isolate. The per cent dialyzable iron in nigerseed protein isolate is higher than soya protein isolate and ionisable iron of most of the oilseeds (Reddy & Hotwani, 1993; Hegde et al. , 2009).…”
Section: Resultsmentioning
confidence: 89%
“…They found that pesticides significantly reduced the zinc content but increased the calcium and potassium contents. Additionally, endosulfan had a more pronounced effect on altering mineral element contents compared to malathion [ 55 ]. The probable reason for this is that pesticides, as exotic stressors, cause a reduction in rice stomatal opening, which in turn results in a decrease in photosynthetic rate and organic matter production, thereby reducing the fat and carbohydrates stored in rice gains [ 56 , 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%